A computational approach to study the optoelectronic properties of F-BODIPY derivatives at the bulk level for photovoltaic applications. (8th January 2020) - Chaudhry, Aijaz Rasool; Muhammad, Shabbir; Haq, Bakhtiar Ul; Laref, A; Al-Sehemi, Abdullah G; Khalid, Muhammad; Irfan, Ahmad
Abstract: The Dipyrrin compounds are recognized as imminent and hi-tech organic semiconductor materials (OSMs) designed for photovoltaic applications owing to low-cost, flexible, and eco-friendly nature. In a latest study, several optoelectronic properties of conjugated F -BODIPY derivatives were studied by using the density functional theory (DFT) at (GGA/PBE) level. This analysis classifies Comp_1 (5, 5-difluoro-1, 37, 9-tetramethyloctahydro-1H, 5H-5l4-dipyrrolo[1, 2-c:2′, 1′-f][1, 3, 2] diazaborinine) as a direct band-gap semiconductor with a band-gap of 2.81 eV. The band-gap of Comp_2 (2-ethyl-5, 5-difluoro-1, 3, 7, 9-tetramethyloctahydro-1H, 5H-5l4-dipyrrolo[1, 2-c:2′, 1′-f][1, 3, 2]diazaborinine) and Comp_3 (2, 8-diethyl-5, 5-difluoro-1, 3, 7, 9-tetramethyloctahydro-1H, 5H-5l4-dipyrrolo[1, 2-c:2′, 1′-f] [1, 3, 2] diazaborinine) are reduced by 1.25 and 1.09 eV, respectively in comparison with parent molecule Comp_1 owing to the influence of p - orbitals of all atoms in crystal structures. The reduction in energy and density of states (DOS) for these compounds in this study validated that band-gap could be improved to a required value for optoelectronic applications by derivatives modeling. Additionally, optoelectronic properties at the solid-state bulk level were also computed. Several features of interest at solid-state bulk level exposed the F -BODIPY derivatives as competent compounds for organic semiconductor devices applications.